IMPLEMENTASI PROGRAM MODERASI BERAGAMA DALAM MENINGKATKAN TOLERANSI DAN KERJASAMA ANTAR WARGA DESA KARYA MAJU - Sundari, Sriy; Ramadan, Mulia (Universitas Negeri Medan, 2025)
This article describes the implementation of a religious moderation program in Karya Maju Village, which aims to strengthen tolerance and cooperation among community members. The activities were carried out through socialization, discussion forums, and collaborative religious practices involving local youth and community leaders. The program encouraged residents to adopt more open and appreciative attitudes toward diversity. The results showed that community members began to interact more cooperatively and respectfully in both religious and social activities. This indicates that the application of religious moderation can be an effective approach to maintaining harmony in a plural society.